2016
DOI: 10.1016/j.kint.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The dipeptide alanyl-glutamine ameliorates peritoneal fibrosis and attenuates IL-17 dependent pathways during peritoneal dialysis

Abstract: Peritoneal dialysis (PD) can result in chronic inflammation and progressive peritoneal membrane damage. Alanyl-Glutamine (Ala-Gln), a dipeptide with immunomodulatory effects, improved resistance of mesothelial cells to PD fluids. Recently, interleukin-17 (IL-17) was found to be associated with PD-induced peritoneal damage. Here we studied the capacity of intraperitoneal Ala-Gln administration to protect against peritoneal damage by modulating IL-17 expression in uremic rat and mouse PD exposure models. Supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 33 publications
8
50
1
3
Order By: Relevance
“…IL-17 activation was recently also linked to the pro-fibrotic inflammatory state associated with in-vivo PDF exposure. This effect was abrogated by AlaGln addition to PDF 43 . Confirmation of long-term effects on IL-6/IL-17 signaling-related increased immune-competence will require treatment of larger numbers of patients over more extended periods.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…IL-17 activation was recently also linked to the pro-fibrotic inflammatory state associated with in-vivo PDF exposure. This effect was abrogated by AlaGln addition to PDF 43 . Confirmation of long-term effects on IL-6/IL-17 signaling-related increased immune-competence will require treatment of larger numbers of patients over more extended periods.…”
Section: Discussionmentioning
confidence: 96%
“…As suggested by our data, the connection with G-protein signaling through regulator of G-protein signaling 4 (RGS4) and RGS16 might modulate leukocyte responsiveness 4042 . G-protein signaling and its connection to the T H 17 response might also link immune-modulatory effects of AlaGln and its recently reported anti-fibrotic properties 43 . Notably, although AlaGln treatment up-regulated the majority of differentially abundant transcripts, those down-stream of IL-17 (CCL2 and TNF-α) were down-regulated by AlaGln, with TNF-α being at the center of one of the top identified interaction networks, consistent with mitigation of acute inflammation, a known immune-modulatory effect of glutamine 39 .…”
Section: Discussionmentioning
confidence: 97%
“…They include, neutral pH, low or ultralow glucose degradation products containing solutions, solutions using alternative osmotic agents, low-sodium solutions and supplementation with the dipeptide alanyl-glutamine. [28][29][30][31] The peritoneal administration of alanylglutamine -a dipeptide with immunomodulatory effects -in uremic rat and mouse PD exposure models showed substantial promise, as it reduced PD-induced peritoneal fibrosis, reduced proinflammatory/fibrotic markers and ameliorated damage, in part by modulating IL-17 expression. 31 At present, however, in spite of demonstrating some beneficial effects in maintaining stability of PSTR, there is no conclusive clinical evidence that the use of more bio-compatible PDS is associated with a lower burden of peritoneal inflammation or improved clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] The peritoneal administration of alanylglutamine -a dipeptide with immunomodulatory effects -in uremic rat and mouse PD exposure models showed substantial promise, as it reduced PD-induced peritoneal fibrosis, reduced proinflammatory/fibrotic markers and ameliorated damage, in part by modulating IL-17 expression. 31 At present, however, in spite of demonstrating some beneficial effects in maintaining stability of PSTR, there is no conclusive clinical evidence that the use of more bio-compatible PDS is associated with a lower burden of peritoneal inflammation or improved clinical outcomes. 32 Notably, data from the GLOBAL Fluid study have shown that the peritoneal levels of the proinflammatory and fibrotic cytokine IL-6 are strongly associated with patients PSTR, 33 confirming a link between local inflammation and membrane function.…”
Section: Discussionmentioning
confidence: 99%
“…In einem PD-Modell in Ratten und Mäusen ist die Zugabe von Alanyl-Glutamin zu einer konventionellen PD-Lösung über 8 Wochen außerdem mit einer signifikanten Reduktion der peritonealen Fibrose, Angiogenese und Zahl der inflammatorischen Zellen sowohl im Dialysatauslauf als auch im Peritoneum verbunden. Diese Effekte werden über eine Reduktion der Interleukin(IL)-17 Expression von T-Helferzellen vermittelt [40].…”
Section: Glutamin Im Tierexperimentsunclassified